2011
DOI: 10.2139/ssrn.1750260
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Occupational Segregation, Glass Ceiling Effects, and Earnings in Managerial Positions: Results of a Fixed Effects Model

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 65 publications
(53 reference statements)
1
23
0
2
Order By: Relevance
“…From the beginning of someone's career, there is some kind of gender-specific self-selection process because women and men have heterogeneous tastes for jobs. Women with family intentions might, for example, invest less in human capital, when long working breaks are scheduled (Achatz et al 2004;Busch and Holst 2011). They might also choose jobs that can be easily combined with family life, such as part-time jobs, jobs close to the nursery and jobs with a high starting wage but smaller returns to experience (Achatz et al 2004;Finzi 2007).…”
Section: Discrimination From the Supply Sidementioning
confidence: 99%
See 1 more Smart Citation
“…From the beginning of someone's career, there is some kind of gender-specific self-selection process because women and men have heterogeneous tastes for jobs. Women with family intentions might, for example, invest less in human capital, when long working breaks are scheduled (Achatz et al 2004;Busch and Holst 2011). They might also choose jobs that can be easily combined with family life, such as part-time jobs, jobs close to the nursery and jobs with a high starting wage but smaller returns to experience (Achatz et al 2004;Finzi 2007).…”
Section: Discrimination From the Supply Sidementioning
confidence: 99%
“…Limited job selection can create occupational segregation, meaning the concentration of men and women in different job categories. The findings in the literature show that the higher the share of women in a certain job sector, the lower the overall wage (e. g., Treiman and Hartmann 1981;England et al 1988;Busch and Holst 2011;Busch 2013). Bertschy et al (2014) found for Switzerland that women earn on average the highest salary in typically female job sectors and less in equally shared or male-dominated job sectors, but less than men in general, regardless of the job sector.…”
Section: Monopsony Powermentioning
confidence: 99%
“…The fraction of the observed gender pay gap explained by occupational segregation varies a lot across studies and countries. The gender share in occupation variable explained between 7 percent and 32 percent of the observed pay gap in the studies on the United States, about 25 percent in the cross-country study on EU-12 countries (European Commission 2002), as much as 50-56 percent in Greece (Karamessini and Ioakimoglu 2007), and as little as 3 percent in Germany (Busch and Holst 2011).…”
Section: Introductionmentioning
confidence: 97%
“…These studies confirm that earnings of both women and men are lower in female-dominated occupations. While a majority of the studies show that the negative effect of working in female-dominated occupations on earnings is much more pronounced for women, studies by Johnson and Salon (1986) and Sorensen (1990) for the United States and Busch and Holst (2011) for Germany found that the negative effect was stronger for men. In Macpherson and Hirsch's (1995) study for the United States, the effect of gender composition on earnings was of similar magnitude for women and men.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation